The Effect Of Using Jakarta Post Headlines And Sub Headlines as Teaching Media Towards The Students Vocabulary Mastery (The Explora, 2022)
This research is about the effect of using Jakarta post headlines as teaching media towards the students’ vocabulary mastery. The objective of the study is to find out whether Jakarta post headlines and sub headlines affects students’ vocabulary mastery. This study was conducted by applying experimental quantitative research. The subject of the study was the second year students of SMP N.17 Medan. The researcher took VIII-4 which consists of 30 students as experimental group using Jakarta post headlines and sub headlines media and VIII-1 which consists of 30 students as control group used conventional method or without Jakarta post headlines and sub headlines. The population of this research was 60 students which consist of two parallel classes. The researcher took both groups as total sampling to see the effect of using Jakarta post headlines and sub headlines as teaching media towards the students’ vocabulary mastery. The data were taken by giving vocabulary test which consists of word completion and matching. The tests were divided into two tests: pre-test and post-test for both experimental and control group. The mean score of pre-test in experimental group is 53.73 and the post-test is 79.86. The mean score of pre-test in control group is 43.86 and the post test is 58.667. It is concluded that the mean score of experimental group is higher than control group. The result that t-calculated > t-table at the level of significance p = 0.01 (3.095>2.660). The alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. It means that Jakarta post headlines and sub headlines can be used as teaching media as alternative to enrich students’ vocabulary mastery at the second year students of Junior High School. key words: Jakarta post headlines and sub headlines, Vocabulary